FULLFILLMENT OF DISABILITY RIGHTS BASED ON DEFINITIONS, LEGAL BASIS, CRITERIA, AND AIMS OF INCLUSIVE EDUCATION IN INDONESIA - Gardiana Karya; Insiatun Insiatun; Nindya Ayu Rizqianti; Putri Kartika Ningsih; Ediyanto Ediyanto; Asep Sunandar; Dzintra IliÅ¡ko (Universitas Ahmad Dahlan, 2021)
One of the Indonesian government's efforts to provide equal education for disabilities is by implementing inclusive education. Inclusive education gives special needs (SEN) students have the same opportunity to get education together in class with the typical students of their age and obtain equal education services. So, inclusive education concept understanding is needed to provide information about inclusive education. Therefore, this article's arrangement provides information about inclusive education's definition, legal basis, characteristics, and aims. The current study method used a literature review of five books and 17 articles. It showed that inclusive education is the education service given to the unique needs students to have equal opportunity to school in the regular school and obtain equal service. The implementation of inclusive education had been regulating by international regulations and, in more detail, regulated by Indonesian government regulations. The characteristics of inclusive education must consider the interests of the disabilities and their flexibility to create an education that could run well and lasts long. In addition to imposing equal educational rights without any differentiation and optimizing special needs students' potential, inclusive education could also increase the interaction of special needs students.